In vitro and in vivo antifungal activity of Minocycline albumin nanoparticles in combination with fluconazole against azole-resistant Candida spp - Lulu An; Xiaowen Huang; Meizhen Zhong; Jiaan Wu; Mei Liu; Liqian Geng; Yongyong Li; Xiuli Wang; Lianjuan Yang; Jingwen Tan (BMC Microbiology)
Abstract Despite the widespread use of fluconazole (FLC) in treating Candida infections, the emergence of drug resistance has become an increasing concern. Our earlier studies showing synergism between minocycline (Min) and azoles were limited by Min’s high required concentrations exceeding clinically achievable plasma levels. To overcome this limitation, we engineered novel bovine serum albumin (BSA)-encapsulated minocycline nanoparticles (Min-NPs). Then we evaluated the physicochemical properties such as size, potential, particle stability, drug loading and toxicity to make sure their efficacy and safety. Using checkerboard dilution assays, we demonstrated that Min-NPs significantly enhanced azole activity against Candida species at substantially lower Min concentrations than previously required. For C. albicans and N. glabrata, under a certain concentration of FLC, the concentration of Min-NPs required to reach 50% MIC is less than 4 µg/mL. When tested in a murine model of systemic candidiasis, Min-NPs combined with FLC showed superior therapeutic efficacy compared to conventional Min and FLC combinations. In summary, the modification of this formulation can enhance the synergistic efficacy of Min, thereby enabling its potential application as an adjunctive therapy for drug-resistant Candida infections. Clinical trial number. Not applicable.